Characteristics of Obstructive Ileus: Literature Review - Ikhsan H, Haerul; Bamatraf, Anis; Laurentz, Happy (Jurnal Biologi Tropis, 2024)
Obstructive ileus or often called bowel obstruction is one of the pathological processes that cause abdominal distress. Abdominal distress is an emergency condition in the abdominal cavity. This condition usually arises suddenly with the main complaint of pain. This study aims to see the characteristics of obstructive ileus. The research design used in this study is a literature review using Google scholar in finding previous related articles. The criteria for related articles used were those published from 2021-2024 and 20 journals were collected. Based on these 20 journals, it was found that the characteristics of obstructive ileus were mostly in adulthood and the elderly, based on gender, many were found in men due to lifestyle, while based on the cause of postoperative adhesions and based on symptoms that abdominal pain, nausea, vomiting, and abdominal distension were clinical features of obstructive ileus sufferers.